Entre os riscos e a coragem de dizer a verdade sobre si: os discursos das sobreviventes de estupro a partir da prática da confissão no Facebook - Nery, Luciana Fernandes (2021)
This thesis has as general objective to investigate the dicourses and modes of subjectivation of women, rape survivors, in confession practices on Facebook. Specifically, we intend to: discuss, from Foucault’s Discursive Studies, the conditions of possibility that legitimize this practice of confession; check out how the discourses around the supremacy of the male sexual power affect the female body and contribute to the naturalization/normalization of rape; trace a historical course of rape in Brazil, in order to understand the jurisdictionalization and a institutionalization of certain discourses around this crime; analyze in a public group of the Facebook the parrhesiastic saying of rape survivors and how they constitute themselves while ethical subjects. We used the archegenealogical method to subsidize our analysis, with emphasis in the third phase of Foucault’s work, but also we used theoretical input of Vigarello (1998, 2012); Schritzmyer e Pandjiarjian (1998), Perrot (2019), Corbin; Courtine (2012), and others. Our research is qualitative with a descriptive-interpretative nature. We selected, as corpus, the confessions presented in the Facebook group “The incredible women that will die twice: survivors’ network”. We collected 86 statements ( 26 in the form of comments) and chose for analysis a total of 52, based on regularity and uniqueness of the statements. We also consider the discursive events with the greatest repercussion in the national scene around rape from 2016 to 2020, the laws, statistics data, public policies and campaigns to combat the violence against women. We verified that the practice of survivors’ confession to the rape represents an act of resistance, an ethical practice of liberty. In addition, the parrhesiastic saying through self-writing relate with self-care and the other and it is surrounded by an ethical responsibility that seeks to encourage other women to report their abusers. At the survivors’ confession, we noticed that the way as these subjects are objectified/subjectified are determined by the relationship that they establish with themselves and with the other and by the relationship with the body and with the sexuality. There are in the survivors’ discourses principles of obedience to the government of the other that contribute to the silencing of rape. The analysis of the corpus presented that the predominance of family members among the rapists can be considered a justification for that women do not report the case to the police and also by the preference for anonymity in the Facebook. We concluded that the discursive practice of confession by rape survivors is not just about talking about themselves, but thinking as the act of saying the truth can provoke fissures in a misogynist and sexist society. We hope that our research can contribute to greater visibility of the rape survivors’ confessions and that their voices to be heard.